KINETICS OF ESTERIFICATION OF LONG-CHAIN ALCOHOL WITH DICARBOXYLIC ACID FOR SYNTHETIC LUBRICANT BASE STOCK PRODUCTION - Auliaannisaa, Sharia
the requirements of industrial machinery, which are superior lubricants performance under extreme conditions and environmental compatibility. The application of conventional mineral oil based lubricants shows inferior performance as a result of the limitations of mineral oil physiochemical properties. However, mineral oil based lubricants are relatively cheap to produce and therefore are economic in comparison to synthetic lubricants. One of the alternatives is diester based lubricants, which held excellent physiochemical properties in a wide range of temperatures and a high resistance of shear stress, oxidative reaction, hydrolysis, and elevated temperature. The study of conversions and kinetics of long-chain alcohol and dicarboxylic acid esterification are conducted to sustain indigenous production of diester on a larger scale. This paper represents the study of dioctadecyl adipate production as a synthetic lubricant base stock through the esterification reaction between octadecanol and adipic acid catalyzed by acid catalyst in the temperature range of 120-????????????????????, under atmospheric pressure for 240 minutes. The effect of various parameters such as acid to alcohol molar ratio (1:2 and 1:4) and catalyst type (H2SO4 98% and PTSA 99%) are tested. Throughout the reaction, the samples are withdrawn every 30 minutes to determine the acid number and the water is continuously removed from the reaction mixture to measure the volume produced. First-order, second-order, and third-order kinetic models are employed to correlate the experimental data. The result is 1:4 molar ratio of adipic acid:octadecanol and H2SO4 catalyst showed most optimum conversion and esterification reaction rate. Conversion value of 71% and 60,5% is obtained with kinetic constants of 4,89×10-5 and 5,04×10-5 for PTSA and H2SO4 catalyst, respectively.